Teaching the Museum: Careers in Museum Education - Mainwaring, Megan (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
This collection of 17 short career-related memoirs and reflections of mid-late career museum professionals provides personal insights into the development of expertise, confidence, and recognition in a museum education career. The book is structured by theme, based on the type of career advice provided in each article.